THE IMPACTS OF ODD-EVEN RESTRICTION POLICY ON TRAVEL BEHAVIOUR - Nuryani Tinumbia; Khusnul Khotimah (Jurnal Infrastruktur, 2021)
In order to reduce traffic congestion, the Government of DKI Jakarta has imposed vehicle restrictions by implementing an odd-even system policy. This study aims to identify travel behaviour of private car users and their perceptions of the odd-even policy. The target respondents were people who live in Jabodetabek and travel in or to the Jakarta area using private cars. Questionnaires were distributed online to the appropriate target respondents. The analysis is descriptive statistics. The result shows that the majority of car users will shift to using public transportation or using motorbikes to travel in or to Jakarta if the road sections affected by the odd-even policy are expanded. But some of them who do not want to shift modes, they prefer to avoid the applied roads. Meanwhile, for some of the users whose economic level is more than adequate will tend to buy a new car, with a different car number plate. For private care users, socialization of odd-even system policy and supervision of violators was considered effective, then the implementation of odd-even system policy on several roads is deemed effective in smoothing traffic flow than before.